2010
DOI: 10.1088/0022-3727/43/50/505103
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer As2Se3/GeS2 quarter wave structures for photonic applications

Abstract: The optical properties of single layers from As2Se3 and GeS2, double-layered stack and quarter-wave multilayer structure consisting of alternating layers from both materials are investigated. For modelling of multilayer coating the thickness dependence of the refractive index of single coatings from both materials is studied. The particularities and scope of application of different spectrophotometric methods for calculation of optical parameters of thin chalcogenide layers are discussed for film thickness, d,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The chalcogenide layers were deposited by thermal evaporation at deposition rate of 0.5 -0.7 nm/s. The X-ray microanalysis showed that the film composition is close to that of the bulk samples (Todorov et al, 2010b).…”
Section: Experimental Procedures For Deposition Of 1d Photonic Crystalsmentioning
confidence: 65%
See 2 more Smart Citations
“…The chalcogenide layers were deposited by thermal evaporation at deposition rate of 0.5 -0.7 nm/s. The X-ray microanalysis showed that the film composition is close to that of the bulk samples (Todorov et al, 2010b).…”
Section: Experimental Procedures For Deposition Of 1d Photonic Crystalsmentioning
confidence: 65%
“…Combinations of Ge-S / Sb-Se (Kohoutek et al 2009) with optical contrast of more than 1 and exposed As 2 Se 3 / GeS 2 with optical contrast more than 0.8 have been already realized. (Todorov et al 2010b). …”
Section: Short Description Of Theory Of Photonic Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison for the refractive indices, n for wavelength λ = 1550 nm, optical band gap and slope parameter B for thin film prepared on rotated substrates and obliquely deposited films at angle 75˚ is given in table 1. Significant variation of the band gap when changing the angle of incidence of the vapours is observed for thin As 10 Ge 30 S 60 layer. The lower values of B for the thin films with columnar structure are due to larger structural disorder.…”
Section: Resultsmentioning
confidence: 95%
“…The program used to calculate n will determine it to an accuracy of  0.5 % for an error in the transmittance of  0.1 % [10]. In figure 2 a comparison is given of the dispersions of the refractive index of thin films deposited normally or obliquely at 75° angle of The reflectance and transmittance spectra wеre used for calculation of the linear absorption coefficient, α and optical band gap, E g through the equations: …”
Section: Resultsmentioning
confidence: 99%